(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article describes in detail some aspects of coaching training diagnostics in education, in which the training stages are: introduction (introduction, goal setting), theoretical part (fundamentals of coaching), practical exercises (role playing, cases), analysis and reflection, types of diagnostics (assessment and analysis) . The result is highlighted separately. A program (scenario) for training is prepared and the stages are explained. “Applying the coaching approach in education” on the subject The full training program (scenario) is detailed.